Molecular subtypes and a prognostic model for hepatocellular carcinoma based on immune- and immunogenic cell death-related lncRNAs - He, Mingang; Gu, Wenchao; Gao, Yang; Liu, Ying; Liu, Jie; Li, Zengjun (Frontiers in Immunology, 2022)
Long non-coding RNAs (LncRNAs) regulate a wide range of functional activities, such as immune response, tumorigenesis, and tumor progression. Immunogenic cell death (ICD) is a type of regulated cell death that causes an effective anti-tumor adaptive response through the activation of dendritic cells and specific T cells. There is an increasing evidence that ICD enhances immunotherapy effectiveness. Therefore, a combination of ICD, immunity, and lncRNA biomarkers may be a promising candidate as a bioindicator for hepatocellular carcinoma (HCC) outcomes. Immune-and immunogenic cell death-related lncRNAs (IICDLs) were identified from The Cancer Genome Atlas and Ensemble databases. IICDLs were extracted from differential expression analysis and univariate Cox analysis to generate molecular subtypes using the package ConsensusClusterPlus. Following that, we created a prognostic signature based on IICDLs and a nomogram based on risk scores. Clinical characteristics, immune landscapes, ICB responses, stemness, and chemotherapy responses were also analyzed for different molecular subtypes and risk groups. A total of 81 IICDLs were identified, and 20 of them were significantly associated with overall survival (OS) in patients with HCC. Cluster analysis divided patients with HCC into two distinct molecular subtypes (C1 and C2), with C1 having a shorter survival time. Four IICDLs (TMEM220-AS1, LINC02362, LINC01554, and LINC02499) were selected to develop a prognostic model that was an independent prognostic factor of HCC outcomes. C1 and the high-risk group had worse overall survival (HR > 1.5, p < 0.01), higher T stage (p < 0.05), clinical stage (p < 0.05), pathological grade (p < 0.05). Additionally, we found that C1 and the high-risk group had low immune cell infiltration (CD4+ T cells, B cells, macrophages, neutrophils, and myeloid dendritic cells), low immune checkpoint genes expression, poor response to ICB therapy, and high stemness. Moreover, different molecular subtypes and risk groups showed significantly different responses to several chemotherapy drugs, such as doxorubicin (p < 0.001), 5-fluorouracil (p < 0.001), gemcitabine (p < 0.001), and sorafenib (p < 0.01). Our study identified molecular subtypes and a prognostic signature based on IICDLs that could be helpful for the prediction of clinical prognosis and treatment response in patients with HCC.